Unstoppable : [the incredible power of faith in action] - Vujicic, Nick (Random House Audio : Books on Tape, 2012)
Being unstoppable is about believing and achieving. It's about having faith in yourself, your talents and your purpose and, most of all, in God's great love and His divine plan for your life. Millions around the world recognize the smiling face and inspirational message of Nick Vujicic. Despite being born without arms or legs, Nick's challenges have not kept him from enjoying great adventures, a fulfilling and meaningful career, and loving relationships.